Measuring efficiency of nations in Multi Sport Events: A case of Commonwealth Games XIX - Mitra Debnath, Roma; Malhotra, Ashish (Naše gospodarstvo/Our economy, 2015)
This paper used a data envelopment analysis (DEA) to measure the performance of the nations participating in the Commonwealth Games. To increase the consistency of the research, multiple models were employed to validate the result, but the nature of the input and output remained same throughout the paper. The objective of this study was to establish some realistic targets in terms of number of players for all participant countries and evaluations of their performance as well as benchmarks against the most efficient country. This study would help the nations optimize the size of their players to maximize the outcome in terms of the number of medals won in sporting events.